Teaching English in Diverse Settings: Lived Experiences of Nepalese ELT Teachers - Saud, Dammar Singh (Far Western Journal of Education, 2025)
This study explores the lived experiences of English Language Teachers in Nepal’s rural, multilingual, and multicultural contexts, focusing on the Darchula district. Adopting a hermeneutic phenomenological approach, the research examines how four secondary-level ELT teachers navigate the pedagogical complexities of multilingual classrooms. Data were collected through semi-structured interviews and classroom observations, and interpreted using thematic analysis. The study is informed by Translanguaging Theory and Vygotsky’s sociocultural perspective, highlighting how teachers draw on students’ linguistic and cultural backgrounds to support learning. t i Findings indicate that multilingual classrooms foster met linguistic awareness, empathy, and cultural sensitivity, enabling teachers to develop adaptive and inclusive teaching strategies. Translanguaging emerged as a key practice to bridge linguistic gaps, enhance participation, and deepen comprehension. Culturally responsive teaching also played a vital role in affirming students’ identities and creating equitable learning spaces. Despite these strengths, teachers reported challenges, including insufficient training in multilingual pedagogies, limited institutional support, language hierarchies, and resource constraints. Participants emphasized the need for professional development that is contextually relevant and addresses both the pedagogical and emotional demands of teaching in diverse settings. This study calls for the integration of multilingual awareness, translanguaging practices, and cultural competence into teacher education in Nepal. By foregrounding rural teachers’ voices, it contributes to the broader discourse on equitable and inclusive language education and offers insights for policy and professional development aimed at enhancing teaching practices in linguistically complex classrooms.